Investigation of Energy Mechanism and Acoustic Emission Characteristics of Mudstone with Different Moisture Contents - Jingdong Jiang; Jie Xu (Shock and Vibration)
Characteristics of energy accumulation, evolution, and dissipation in conventional triaxial compression of mudstones with different moisture contents were explored. Stress-strain relations and acoustic emission (AE) characteristics of the deformation and failure of rock specimens were analyzed. The densities and rates of stored energy, elastic energy, and dissipated energy under different confining pressures were confirmed. The results demonstrated that the growth rate of absorbed total energy decreases with the increase of moisture content, indicating that the higher the moisture content is, the less the total energy mudstone samples absorb. The dissipated energy of the soaking sample, by contrast, has the first increase speed, and natural sample comes second at the beginning. When entering the crack stable development stage, the dry sample has the fastest growing rate of dissipated energy, meaning that dissipated energy used for crack propagation gradually decreases with the increase of moisture content. The AE signals significantly enhance at the initial compression stage and plastic deformation stage with the moisture content decreasing. The AE location events at the failure moment decrease as the moisture content increasing. The time that the maximum AE even rate appears is slightly lagged behind the macroscopic failure time, and the AE even rates increase with the decrease of confining pressure. The above results indicate that the water erosion process on rock reduces the cohesive energy and cohesive force, destroys the micromechanical structure, and minimizes the energy states of rock.